Automatic Mode-Matching Method for MEMS Disk Resonator Gyroscopes Based on Virtual Coriolis Force - Zhihu Ruan; Xukai Ding; Zhengcheng Qin; Jia Jia; Hongsheng Li (Micromachines, 2020)
An automatic mode-matching method for MEMS (Micro-electromechanical Systems) disk resonator gyroscopes (DRGs) based on virtual Coriolis force is presented in this paper. For this mode-matching method, the additional tuning electrodes are not required to be designed, which simplifies the structure design. By using the quadratic relationship between the driving voltage and the electrostatic force, the virtual Coriolis force is obtained by applying an AC voltage whose frequency is half of the driving mode resonant frequency to the sense electrode. The phase difference between the virtual Coriolis force and the sense output signal is used for mode-matching. The structural characteristics and electrode distribution of the DRG are briefly introduced. Moreover, the mode-matching theories of the DRG are studied in detail. The scheme of the mode-matching control system is proposed. Simultaneously, the feasibility and effectiveness of the mode-matching method are verified by system simulation. The experimental results show that under the control of mode-matching at room temperature, the bias instability is reduced from 30.7575 <semantics> ° </semantics> /h to 2.8331 <semantics> ° </semantics> /h, and the Angle Random Walk (ARW) decreases from 1.0208 <semantics> ° / <msqrt> h </msqrt> </semantics> to 0.0524 <semantics> ° / <msqrt> h </msqrt> </semantics> . Compared with the mode mismatch condition, the ARW is improved by 19.48 times.